Association analysis of B7‐H3 and B7‐H4 gene single nucleotide polymorphisms in susceptibility to ankylosing spondylitis in eastern Chinese Han population. (23rd September 2021) - Chen, Yuting; Yang, Hui; Xu, Shanshan; Shen, Jiran; Xu, Wei; Shao, Ming; Pan, Faming
Abstract: This study was conducted to describe the association between the genetic variation of the recently identified immune checkpoint molecules B7‐H3 and B7‐H4, and the susceptibility to ankylosing spondylitis (AS). Two single nucleotide polymorphisms (SNPs) of B7‐H3 gene and three SNPs of B7‐H4 gene were genotyped in 649 AS patients and 646 age‐ and sex‐matched healthy controls. Allele, genotype frequencies and different inheritance models were performed to calculate odds ratios (ORs) and 95% confidence intervals (CIs), and the demographic and clinical parameters of patients were recorded. Our data indicated that B7‐H4 rs10801935 and rs3738414 polymorphisms were correlated with AS susceptibility. In the stratification analyses, the minor A allele and GA genotype of B7‐H4 rs3738414 increased the risk of AS in male patients (OR = 1.244, 95%CI = 1.026–1.508; OR = 1.453, 95%CI = 1.120–1.886, respectively). However, the association did not reach statistical significance after Bonferroni correction. Furthermore, haplotype analysis revealed that B7‐H4 haplotype block TAG was a risk factor for the onset of AS (OR = 1.190, 95%CI = 1.020–1.389). These findings suggested that B7‐H4 gene polymorphism may contribute to AS susceptibility in eastern Chinese Han population.